Rattus fuscipes - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Rattus fuscipes (Waterhouse, 1839). Zool. Voy. H.M.S. "Beagle," Mammalia, p. 66. TYPE LOCALITY: Neotype from Australia, Western Australia, Albany, "Little Grove" on Princess Royal Harbor, 4 mi S Mt Melville; holotype was lost (Mahoney and Richardson, 1988; Taylor and Horner, 1973). DISTRIBUTION: Coastal, subcoastal, and offshore islands of SW Western Australia; S coast from Eyre Peninsula in South Australia to W Victoria; coastal and subcoastal Victoria from Otway Peninsula north to near Rockhampton in Queensland; coastal Queensland from Townsville to Cooktown (see map in Taylor and Horner, 1973:15). SYNONYMS: assintilis, brazenori, coracius, glauerti, greyii, manicatus, mondraineus, murrayi, peccatus, pelori, ravus. COMMENTS: Taylor and Horner (1973) suggested, on morphological grounds, that the Queensland population of R. fuscipes (coracius) has a common ancestry with Queensland R. leucopus, a hypothesis reasserted by Taylor et al. (1982, 1983). This relationship, however, is not supported by either chromosomal (Dennis and Menzies, 1978) or biochemical data (Baverstock et al., 1983a, 1986). See Taylor and Calaby (1988a, Mammalian Species, 298). Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on pages 652-653, DOI: 10.5281/zenodo.7353098